Gut microbiome characteristics of comorbid generalized anxiety disorder and functional gastrointestinal disease: Correlation with alexithymia and personality traits - Guo, Xunyi; Lin, Feng; Yang, Fengjiao; Chen, Jing; Cai, Weixiong; Zou, Tao (Frontiers in Psychiatry, 2022)
Objective The aim of this study was to investigate the characteristics of intestinal flora in patients with functional gastroenteropathy and generalized anxiety disorder (GAD) and the relationship between intestinal flora and psychological factors. Materials and methods From March 2020 to December 2020, a total of 35 patients with functional gastroenteropathy and generalized anxiety disorder, 30 healthy controls, 16 patients with functional gastroenteropathy, and 44 patients with generalized anxiety disorder were selected from the Affiliated Hospital of Guizhou Medical University. Fecal samples were collected from each group, and the related psychophysiological factors scales (Hamilton Anxiety Scale, Hamilton Depression Scale, Neurotic Personality Questionnaire, concept of illness questionnaire, Toronto Alexithymia Scale, Severity of Physical Symptoms Scale, and Cognitive Emotion Regulation Questionnaire) were improved. 16S rRNA high-pass sequencing was used to determine the correlation between intestinal flora changes and functional gastroenteropathy with generalized anxiety disorder. Then, the scale and gut microbiota results were analyzed for correlation to determine the correlation between personality traits and gut microbiota. Results We found similar intestinal microbiota in patients with functional gastroenterology, generalized anxiety disorder, and functional gastroenteropathy with generalized anxiety disorder. But the relative abundance of Clostridium was significantly increased in patients with functional gastrointestinal disease (FGID) and generalized anxiety. The relative abundance of Haemophilus influenzae was significantly increased in patients with functional gastrointestinal disease without a generalized anxiety disorder. The intestinal microecological composition was significantly correlated with personality traits. Conclusion Functional gastrointestinal disease comorbidity GAD may be related to an increase in the relative abundance of Fusobacterium. FGID non-comorbidity GAD may be related to the increased relative abundance of Hemophilus. The increased relative abundance of Fusobacterium and Megamonas is associated with personality traits such as difficulty describing feelings and difficulty identifying feelings, neuroticism, and negative cognition of disease.